Features of the Course of Atrial Fibrillation in Patients with the History of COVID-19: Impact on the Possibility and Tactics of Restoring Sinus Rhythm - Stasyshena, Oksana V.; Sychov, Oleg S. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. Atrial fibrillation (AF) is a potentially life-threatening complication of infection. In general, AF has a high prevalence in elderly population with cardiovascular risk factors and comorbidities. Thus, the presence of AF correlates with adverse outcomes in patients with previous coronavirus disease (COVID-19) which deserves increased attention and should be appropriately treated to prevent adverse outcomes. The aim. To analyze the prevalence and clinical course of AF in hospitalized patients after COVID-19 to determine approaches to restoring sinus rhythm. Materials and methods. The study included 179 patients with various types of heart rhythm and conduction disorders who suffered from COVID-19 and were hospitalized to the Department of Clinical Arrhythmology and Electrophysiology of the National Scientific Center “The M.D. Strazhesko Institute of Cardiology, Clinical and Regenerative Medicine of the NAMS of Ukraine” from 09/20/2020 to 12/21/2021. 116 patients were hospitalized with AF who suffered from coronavirus infection between 1 and 12 months ago (5.1 ± 0.2 months on average). Other heart rhythm and conduction disorders were the cause of hospitalization for 63 patients (35.2%). The first group was formed by 36 people (31%) in whom AF occurred after coronavirus infection. The second group included 25 patients in whom the form of AF changed, namely: there was a transition from paroxysmal form of AF to persistent AF, or persistent AF to a permanent form of AF. The third group included 55 patients in whom the form of AF did not change. However, in the third group, two subgroups were formed: 3A consisting of 35 patients, in whom, although the form of AF did not change, the frequency or duration of paroxysms increased, and 3B, which included 20 patients without significant changes in the course of AF. As a control group, 49 patients with AF without a history of coronavirus infection were examined. Results. In most patients (65%), the reason for hospitalization was AF. The first recorded paroxysms of this arrhythmia were recorded in 31% of patients 2 months after the coronavirus infection. In this group, more than half of the cases (58.4%) were patients with persistent AF, and 8.3% of those hospitalized failed to restore sinus rhythm. In those who had AF before COVID-19, 75% of its course worsened: the frequency or duration of paroxysms increased. The persistent form of AF was dominant and occurred after a previous infection in 58% of cases. In patients who had AF before COVID-19, its course worsened (in 76% of the examined persons) after the infection. Patients with a history of coronavirus infection had more frequent use of drug therapy, which is probably due to the delayed time of hospitalization to the clinic from the onset of the paroxysm. Conclusion. AF is the most common arrhythmia and has a worse course in hospitalized patients after coronavirus infection.